A Analisis Problematika Guru dalam Mengintegrasikan Biologi dengan Islam di Madrasah Aliyah Negeri Kabupaten Pasaman Barat: The - Amanda puteri; Ardi Ardi (LP2M UIN Ambon, 2025)
Biology learning in Madrasah Aliyah tends to be separated from islamic values. This study focuses on the challenges feced by teachers in integrating biology with islam teachings, aiming to uncover various obstacles encountered by biology teachers in state Madrasah Aliyah Pasaman Barat. The research employs a gualitative descriptive method with a population of biology teachers, and data collection through in depth interviews and classroom observations. The analysis result reveal problems such as limited integrative media constrained learning time. And teachers competency gaps in integrating biology with islam in conclusion, teacher training and the development of structured teaching materials based on biology-islam integrations are need to ad dress these issues.